1995
DOI: 10.1111/j.1528-1157.1995.tb05995.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Adverse Effects of Established and New Antiepileptic Drugs*

Abstract: Antiepileptic drug (AED) selection is based primarily on efficacy for specific seizure types and epileptic syndromes. However, efficacy is often similar for the different AEDs, and other properties such as adverse effects, pharmacokinetic properties, and cost may also be of importance. For idiopathic generalized epilepsies with absence, tonic-clonic, and myoclonic seizures, the AED of choice is valproate (VPA). Secondarily generalized epilepsies with tonic, atonic, and other seizure types are difficult to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 92 publications
0
40
0
3
Order By: Relevance
“…The current therapy of epilepsy with modern antiepileptic drugs is associated with side effects, dose-related and chronic toxicity, as well as teratogenic effects, and approximately 30% of the patients continue to have seizures with current antiepileptic drugs therapy [2][3][4] . Traditional systems of medicine are popular in developing countries and up to 80% of the population relies on traditional medicines or folk remedies for their primary health care need 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The current therapy of epilepsy with modern antiepileptic drugs is associated with side effects, dose-related and chronic toxicity, as well as teratogenic effects, and approximately 30% of the patients continue to have seizures with current antiepileptic drugs therapy [2][3][4] . Traditional systems of medicine are popular in developing countries and up to 80% of the population relies on traditional medicines or folk remedies for their primary health care need 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Today, the primary use of the benzodiazepines as anticonvulsants is in the acute treatment of status epilepticus. Although effective as broad-spectrum antiseizure drugs, the clinical utility of the barbiturates is limited by the development of cognitive impairment and behavioral modifications [for reviews, see Devinsky (1995) and Mattson (1995)]. …”
mentioning
confidence: 99%
“…The results of this study seem to shed some light on the nature of drug resistance, which is observed among a prominent proportion of patients with epilepsy (26). The administration of subconvulsive doses of NMDA or kainate may be considered the factor reflecting the increased level of endogenous EAA agonists such as glutamate and its analogues.…”
Section: Resultsmentioning
confidence: 77%